On the possibility of obtaining a beam of heavy ions in the form of an “open umbrella” with subsequent deposition in the separator manifold - Yuferov, V.B.; Katrechko, V.V.; Vinnikov, D.V.; Tkachev, V.I.; Sharyi, S.V.; Ozerov, O.M.; Sorokina, D.D. (Problems of Atomic Science and Technology, 2023)
The study of SNF reprocessing is impossible without obtaining and studying a multicomponent, low-energy and complex ion beam of an “umbrella” shape. The beam is obtained from a plasma flow created in a plasma source (PS) with a magnetic field of about 3 T, flowing along the axis into a weak magnetic field, at a level of 0.1…0.5 T. At the same time, its density decreases, and the entire energy of the plasma is converted into a jet directed along the axis. To randomize the particles of the jet plasma, a reflecting magnetic field is further placed on the axis. Without changing direction, the plasma flows in a hollow magnetic force tube around a solenoid with a reverse magnetic field. In this region, ions are drawn out in the radial direction towards the annular hole of the “pocket”. The target ions, M (230-277) follow umbrella trajectories and, being neutralized, are deposited in the “pocket” on the inner walls, the remaining ∼ 3% are scattered and remain on the walls of the separator. Вивчення переробки ВЯП неможливе без отримання та вивчення багатокомпонентного низькоенергетичного та складного іонного пучка “парасолькової” форми. Пучок виходить з потоку плазми, створеного в джерелі плазми (ДП) з магнітним полем близько 3 Тл, далі втікає по осі в слабке магнітне поле, на рівні 0,1…0,5 Тл. Його щільність зменшується, і вся енергія плазми перетворюється на струмінь, спрямований уздовж осі. Для хаотизації частинок струминної плазми на осі додатково розміщується магнітне поле відбивного соленоїда. Не змінюючи напрямки, плазма тече в порожній магнітній силовій трубі навколо соленоїда зі зворотним магнітним полем. У цій області іони витягуються у радіальному напрямку до кільцевого отвору “кишені”. Цільові іони М (230-277) слідують “парасольковими” траєкторіями і, нейтралізуючись, осідають у “кишені” на внутрішніх стінках. А решта, ∼ 3%, розсіюються і залишаються на стінках сепаратора.